2014
DOI: 10.1097/ypg.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between dopamine-β hydroxylase gene and a history of suicide attempt in schizophrenia

Abstract: The amplicon size analysis proved to be the most accurate method using the haplotype as a possible genetic marker for future testing. Although the results were not significant, further molecular analyses of the DBH gene and other candidate genes can clarify the utility of the molecular phase in psychiatric genetics and personalized medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Our finding showed that DβH 5′‐Ins/Del polymorphism might not directly contribute to suicide attempts in patients with chronic schizophrenia. This finding was consistent with a study reporting that this polymorphism did not play a role in suicide attempts with chronic schizophrenia in the European population (Howe et al, 2014). Another study has reported that DβH rs2519152 polymorphism was not related to suicide attempts in subjects with psychiatric disorders (Murphy et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding showed that DβH 5′‐Ins/Del polymorphism might not directly contribute to suicide attempts in patients with chronic schizophrenia. This finding was consistent with a study reporting that this polymorphism did not play a role in suicide attempts with chronic schizophrenia in the European population (Howe et al, 2014). Another study has reported that DβH rs2519152 polymorphism was not related to suicide attempts in subjects with psychiatric disorders (Murphy et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Any one of these DβH polymorphisms, such as rs1611115, rs1108580, rs2519152, and rs129882 was not significantly associated with suicidal behavior in alcohol‐dependent patients (Nedic Erjavec et al, 2014; Preuss et al, 2013). However, the DβH haplotype including DβH 5′‐del allele was reported to influence suicide attempts in chronic schizophrenia (Howe et al, 2014). Also, a study supported a significant relationship between DβH haplotype (including rs1611115, rs1108580, rs2519152, and rs129882) and suicidal behavior in alcohol‐dependent patients (Preuss et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this meta-analysis, the lifetime prevalence of SA in BD (33.9%; 95% CI 31.3–36.6%) was significantly higher than in the general population (0.8%; 95% CI 0.7–0.9%) (Bernal et al ., 2007; Cao et al ., 2015) and in schizophrenia (14.6%; 95% CI 9.1–22.8%), but was only slightly higher than the figures found in major depression (31%; 95% CI 27–34%) (Howe et al ., 2014; Dong et al ., 2017, 2018). The higher risk of SA in BD compared to major depression relates to the differences in clinical profile between both disorders (Szadoczky et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that the polymorphism in the 5′ untranslated region of DRD1 is associated with the mediation of the therapeutic response to antipsychotics,11 Moreover, present studies1214 show that deficits in the DRD1 transmission are associated with the cognitive and negative symptoms of schizophrenia and that there is a significant decrease in DRD1 expression in the basal ganglia of schizophrenic patients 15. In contrast, some studies have reported that there was no genetic association between the DRD1 gene and the risk of schizophrenia 1618. Therefore, the role of the DRD1 gene in schizophrenia remains controversial, and a consistent conclusion has yet to be achieved.…”
Section: Introductionmentioning
confidence: 69%